Hubungan Maternal Dietary Diversity terhadap Minimum Acceptance Diet pada Anak dalam Pencegahan Stunting: Systematic Review: Hubungan Maternal Dietary Diversity terhadap Minimum Acceptance Diet pada Anak dalam Pencegahan Gizi Buruk di Negara Berkembang: Systematic Review - Atmaka, Dominikus Raditya; Wulandari, Fatqiatul; Dhorta, Nandia Firsty; Rachmah, Qonita; Setyaningtyas, Stefania Widya; Rifqi, Mahmud Aditya; Diana, Rian; Fitria, Anisa Lailatul; Pratiwi, Azizah Ajeng; Simangunsong, Tiara Tivany; Haryana, Nila Reswari; Nastiti, Aliffah Nurria; Agustin, Asri Meidyah (Amerta Nutrition, 2024)
Background: The MAD in children has an important role in preventing the risk of undernutrition. MAD in children is often associated with MDD in mothers because the mother's consumption pattern continues to feed the child who is born. Objectives: This systematic review aims to examine the relationship between MDD in mothers and MAD in children, and its role in undernutrition prevention. Methods: Articles were selected using the PRISMA method. Articles were obtained from Sciencedirect, Medline, and Embase in the 2017-2022 timeframe without data restrictions. The vocabulary used in the search is "Maternal Dietary Diversity" and "Minimum Acceptable Diet", and undernutrition, and only researched articles in English. Table matriculation was carried out to obtain an overview of the relationship between MDD in mothers and children's MAD in undernutrition prevention. Discussion: Research from 7 selected studies was conducted in five developing countries with high levels of food insecurity. Samples were obtained of 167 to 10,291 children aged 6-59.9 months. Six studies indicate the level of food insecurity in the area studied. Four of the seven studies showed significant results between MDD in mothers with MAD and undernutrition in children. Conclusions: Maternal MDD has a significant role in MAD in children and can be one of the factors that influence undernutrition, especially in developing countries which are highly food insecure.